Motivasi Belajar Dari Rumah (Study From Home) Mahasiswa STAI Denpasar Bali Masa Pandemi Covid-19 - Rusmayani, Rusmayani (Ngabari: Jurnal Studi Islam dan Sosial, 2020)
This study was conducted with the purpose to determine motivation study from home, STAI Denpasar Bali students during the Covid-19 Pandemic, where the learning process from home starts in the third week of March 2020 until now. This study had implemented the method of survey and quantitative in nature. The number of 170 students consisting of the Management of Islamic Education, Islamic Religious Education, and Sharia Economics study program, were selected randomly as samples. A set of questionnaires was used as a research instrument. The data obtained were analyzed descriptively using frequency, percentage, and mean score in order to identify the level of motivation students study from home. The study found that average student learning motivation from home is in the sufficient category, which is 38.82 percent, this proves that even though there is the Covid-19 Pandemic struck, it did not decrease the learning motivation of STAI Denpasar students, and the appreciation given by the lecturer during the learning process from the house took place and the conducive learning environment created by lecturers and institutions was able to motivate students during learning from home during the Covid-19 Pandemic.